A simple model of Brexit under oligopoly - David R. Collie (Cardiff University, Cardiff Business School, 2017)
The welfare effects of Brexit on the UK, the EU27 and the rest of the world are analysed in a model of international trade under oligopoly. A hard Brexit where the UK trades according to WTO rules is shown to decrease total UK welfare, to have an ambiguous effect on total EU27 welfare, and to increase total welfare in the rest of the world. Unilateral free trade for the UK is shown to decrease total UK welfare, to increase total EU27 welfare, and to increase total welfare in the rest of the world. A free trade agreement with the rest of the world rather than the EU27 will be beneficial, ceteris paribus, if the rest of the world market is larger than the EU27 market; if the rest of the world tariff is larger than the EU27 tariff; and if firms in the rest of the world have higher costs than EU27 firms. It will not be beneficial if trade between the UK and the rest of the world is more costly than trade between the UK and the EU27 as is likely to be the case since the EU27 is close to the UK.
Keywords: F12; F13; L13; 330; Brexit; Oligopoly; International Trade; Tariffs; EU